PRECISENESS OF SATELLITE NAVIGATION SYSTEM GPS AND ITS AVAILABILITY UNDER CRITICAL CONDITIONS (Perner's Contacts, 2009)
The paper is aimed on accuracy of location determination through satellites called GNSS (Global Navigation Satellite Systems). It generally describes the principles of these systems working and provides information about cause of mistakes made during GPS location determination. It also experimentally checks basic parameters of modern reciever GPS.
Keywords: GALILEO; PRN code; correlation; multipath; receiver Magellan MMCX